ASSOCIATION OF DRY EYES WITH TYPE AND DEMOGRAPHICS OF EYE COSMETICS USERS - Amir Zeb Khan; Bushra Aaqil; Uzma Bibi; Bushra Mustafa; Qazi Maaz ul Haq; Ammara Sadiq (Journal of Ayub Medical College Abbottabad, 2024)
Background: Eye makeup is applied to make the eyes attractive, improving self-confidence and personal appearance. However, their regular use might be harmful effects to the eyes. This research was done to report the frequency of dry eyes (DEs) among eye cosmetic users and to find association of severity of DE with type of cosmetics and demographics of these patients. Methods: It was a cross sectional study conducted on 141 female patients attending eye OPD of Ayub Teaching Hospital Abbottabad with symptoms suggestive of dryness of eyes. All these women were using different types of eye cosmetics and had no previous history of dry eyes. Ophthalmic examination was performed by a single Eye specialist for confirmation of diagnosis of dry eyes in these women according to Japanese diagnostic criteria. Data was collected on a predesigned structured questionnaire and analyzed on SPSS-23. Results: A total of 83(58.9%) women had DEs among 141 female eye cosmetics users. Mild dryness was present in 3(2.1%), moderate in 16(11.3%) and severe in 65(45.4%). DEs was associated with age (p<0.001), occupation (p<0.001), type of eye make-up used (p<0.001), duration of application (p 0.009), frequency of eye make-up usage (p 0.05), cleanser usage (p 0.009) and removal before sleeping (p 0.005). Conclusion: DEs was quite common among eye cosmetic users in our set up and severe dryness being most frequent. It was associated with multiple demographic and eye cosmetics related variables.